Mechanistic approach for expeditious and solvent-free synthesis of alpha-hydroxy phosphonates using potassium phosphate as catalyst - Kulkarni, Makarand A.; Lad, Uday P.; Desai, Uday V.; Mitragotri, Satish D.; Wadgaonkar, Prakash P. (Comptes Rendus Chimie, 2013)
An extremely simple, high yielding, highly rapid and solvent-free protocol has been described for hydrophosphylation of aldehydes using potassium phosphate as catalyst. Easy commercial availability of the reusable catalyst, operational simplicity at ambient temperature and avoidance of conventional work-up as well as purification procedure makes this solvent-free protocol a near-ideal synthesis. (C) 2012 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.
Keywords: alpha-hydroxy phosphonates; Hydrophosphylation; Potassium phosphate; Solvent-free

Modulation of charge carrier mobility by side-chain engineering of bi(thienylenevinylene)thiophene containing PPE-PPVs - Jadhav, Rupali R.; Camaioni, Nadia; Oppelt, Kerstin; Tinti, Francesca; Gazzano, Massimo; Fattori, Valeria; Wadgaonkar, Prakash P.; Rathgeber, Silke; Hoppe, Harald; Egbe, Daniel A. M. (RSC Advances, 2016)
Four 2-dimensional conjugated poly(p-phenylene-ethynylene)-alt-poly(p-phenylene-vinylene) polymers containing a lateral bi(thienylenevinylene)thiophene unit (BTE-PVs) were synthesised and characterised. The investigated polymers share the same conjugated structure, but differ in the anchoring positions of solubilising linear octyloxy/branched 2-ethylhexyloxy side-chains. UV-vis spectra of the polymers in dilute chloroform solutions and as thin films were studied. X-Ray diffraction patterns as well as the bulk charge transport of polymer films cast from chlorobenzene solutions were also investigated. A dramatic effect of the solubilising side-chains on the charge carrier mobility of BTE-PV films was observed, with bulk hole mobility values ranging between 1.3 x 10(-5) cm(2) V-1 s(-1) and 2.2 x 10(-2) cm(2) V-1 s(-1), which is not ascribable to evident structural variations of the polymer films. It is shown that the combination of linear octyloxy and branched 2-ethylhexyloxy side-chains is favorable for the charge transport properties of BTE-PVs, compared to the incorporation of only linear or only branched side-chains.

Mechanism of the formation of microphase separated water clusters in a water-mediated physical network of perfluoropolyether tetraol - Deshpande, Ashwini A.; Torris, Arun A. T.; Pahari, Swagata; Menon, Shamal K.; Badiger, Manohar V.; Rajamohanan, P. R.; Wadgaonkar, Prakash P.; Roy, Sudip; Tonelli, Claudio (Soft Matter, 2018)
Perfluoropolyether tetraol (PFPE tetraol) possesses a hydrophobic perfluoropolyether chain in the backbone and two hydroxyl groups at each chain terminal, which facilitates the formation of hydrogen bonds with water molecules resulting in the formation an extended physical network. About 3 wt% water was required for the formation of the microphase separated physical network of PFPE tetraol. The mechanism responsible for the microphase separation of water clusters in the physical network was studied using a combination of techniques such as NMR spectroscopy, molecular dynamics (MD) simulations and DSC. MD simulation studies provided evidence for the formation of clusters in the PFPE tetraol physical network and the size of these clusters increased gradually with an increase in the extent of hydration. Both MD simulations and NMR spectroscopy studies revealed that these clusters position themselves away from the hydrophobic backbone or vice versa. The presence of intra-and inter-chain aggregation possibility among hydrophilic groups was evident. DSC results demonstrated the presence of tightly and loosely bound water molecules to the terminal hydroxyl groups of PFPE tetraol through hydrogen bonding. The data from all the three techniques established the formation of a physical network driven by hydrogen bonding between the hydrophilic end groups of PFPE tetraol and water molecules. The flexible nature of the PFPE tetraol backbone and its low solubility parameter favour clustering of water molecules at the terminal groups and result in the formation of a gel.

Methoxyl-containing hyper-crosslinked polymer from largely bio-based biphenyl methyl ether and its application in lithium-sulfur battery - Wale, Apparav K.; Das, Anoushka K.; Patil, Nita R.; Shelke, V. Manjusha; Ambade, V. Ashootosh; Wadgaonkar, Prakash P. (Reactive & Functional Polymers, 2025)
A new biphenyl methyl ether viz 2,2 `,3,3 `-tetramethoxy-5,5 `-bis(methoxymethyl)-1,1 `-biphenyl (TBMB) was synthesized starting from vanillin via three-step reaction sequence. The self-polycondensation of TBMB by employing two Bronsted acid catalysts, viz, p- toluenesulfonic acid (PTSA) and trifluoromethanesulfonic acid (TFSA) led to the formation of organic hyper-crosslinked polymers (HCPs) containing built-in methoxyl groups. HCPs were characterized by FTIR, solid state 13 C NMR, XPS, XRD, TGA, BET, and FESEM analysis techniques. HCPs synthesized using PTSA (HCP-PTSA) and TFSA (HCP-TFSA) exhibited a Brunauer-Emmett-Teller (BET) surface area of 480 +/- 5 and 590 +/- 4 m2/g, respectively and consisted of hierarchical pore structures with both micropores and mesopores. HCP-TFSA was evaluated as an active coating layer on conventional polypropylene (PP) separator in lithium-sulfur batteries to suppress the polysulfide shuttling on account of the ability of methoxyl groups to anchor soluble polysulfide species via coordination. The significant polysulfide adsorption capacity and improved cycling stability with a capacity of 617.2 mAh g- 1 at 0.5C and 99% capacity retention highlighted the potential of porous HCP containing built-in methoxyl groups in the development of attractive lithium-sulfur battery systems.
Keywords: Active coating layer; bio-based; Biphenyl methyl ether; Hyper-crosslinked polymer; lithium-sulfur battery; Methoxyl groups; Self-polycondensation